Reason and inspiration in Islam: theology, philosophy and mysticism in Muslim thought ; essays in honour of Hermann Landolt - Landolt, Hermann; Lawson, Todd (In association with The Institute of Ismaili Studies, 2005)
Central to the current debates on the nature and direction of Islam Highly topical and relevant to the 'Islam and Modernity issue Contributors include blue-chip academics In all the current alienating discourse on Islam, so often depicted as a source of extremism and fanatic violence, this book takes a timely and refreshing look at the traditions of Islamic mysticism, philosophy and intellectual debate in a series of diverse and stimulating approaches. It tackles the major figures of Islamic thought, such as Ibn Arabi, al-Farabi, Ibn Sina and al-Ghazali, as well as shedding light on hitherto u